Characterization of the sedimentary organic matter preserved in Messel oil shale by bulk geochemistry and stable isotopes - Bauersachs, T.; Schouten, S.; Schwark, Lorenz (Elsevier Science BV, 2014)
We investigated a 150 m thick drill core section of Messel oil shale using bulk geochemical and stable isotope techniques in order to determine the organic matter sources and the environmental conditions that prevailed during the deposition of the lacustrine sequence. High Corg values (on average 27%) indicate that the Messel oil shale has likely been deposited under highly productive conditions and/or in an environment largely free of oxygen, which suggests a permanent stratification of the paleolake and prolonged periods of bottom water anoxia. Low stable nitrogen isotope values (ca. + 1 to + 2‰), observed at the transition from holomictic to meromictic conditions, suggest a brief period of an increased contribution of diazotrophic, possibly heterocystous, cyanobacteria that proliferated under the stagnant conditions. The basal oil shale unit (Lower Messel-Formation) is characterized by generally high HI values (> 570 mg HC/g Corg) and molar Corg/Ntot ratios (> 35) that evidence an increased loading of terrestrial organic matter to the lake system, which is hypothesized to be dominated by the lipid-rich constituents of vascular plants.The oil shale of the mid-section (Middle Messel-Formation) is characterized by carbon isotope excursions towards comparatively heavy δ13Corg values of − 24‰ that together with slightly lower Corg/Ntot ratios (ca. 30) of this interval are taken as evidence for a higher loading of aquatic-derived organic matter to the paleolake. The uppermost part of the Middle Messel-Formation displays decreasing δ13Corg and concomitantly high δ15Ntot values, which is interpreted to indicate an increased importance of bacterial driven processes (such as methanogenesis, methanotrophy and denitrification) in the paleolake system. Our results thus indicate that the Eocene maar lake received organic matter from various autochthonous and allochthonous sources with contributions of each source varying significantly over the lake's existence.